2020
DOI: 10.1002/jso.26304
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of superior segmentectomy versus lower lobectomy for superior segment Stage I non‐small‐cell lung cancer are equivalent: An analysis of 196 patients at a single, high volume institution

Abstract: ObjectivesTo determine if superior segmentectomy has equivalent overall (OS), disease‐free (DFS), and locoregional‐recurrence‐free survival (LRFS) to lower lobectomy for early‐stage non‐small‐cell lung cancer (NSCLC) in the superior segment.MethodsWe retrospectively reviewed all Stage 1 lower lobectomies for superior segment lesions and superior segmentectomies at our hospital from 2000 to 2018. Comparison statistics and Cox hazard modeling were performed to determine differences between groups and attempt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The National Comprehensive Cancer Network suggests segmentectomy for patients with poor pulmonary reserve, for which lobectomy is not possible. A number of studies have shown that segmentectomy in patients with early-stage NSCLC can better protect lung function after surgery, which is of great significance for patients with basic pulmonary diseases, such as chronic bronchitis and emphysema, or elderly patients with poor lung function [ 14 16 ]. Data from this study showed that 3 days after surgery, the FEV1, FVC, and MVV levels in both groups were lower than those before surgery, but these levels in the observation group were higher than those in the control group ( P < 0.05), indicating the advantages of thoracoscopic pulmonary segmentectomy to protect lung function.…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network suggests segmentectomy for patients with poor pulmonary reserve, for which lobectomy is not possible. A number of studies have shown that segmentectomy in patients with early-stage NSCLC can better protect lung function after surgery, which is of great significance for patients with basic pulmonary diseases, such as chronic bronchitis and emphysema, or elderly patients with poor lung function [ 14 16 ]. Data from this study showed that 3 days after surgery, the FEV1, FVC, and MVV levels in both groups were lower than those before surgery, but these levels in the observation group were higher than those in the control group ( P < 0.05), indicating the advantages of thoracoscopic pulmonary segmentectomy to protect lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Adjusted NRCs of segmentectomy or wedge vs. lobectomy in apparently healthy patients are shown in Table 1 (16,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52), Table 2 (16,36,42,47,48,50,(53)(54)(55)(56)(57)(58)(59)(60)(61)(62), Table 3 (36,47,48,50,(63)(64)(65)(66) and Figures S2-1…”
Section: Survivalmentioning
confidence: 99%
“…For abbreviations, footnotes, explanation of adjustment for confounding see legend for Table 3. Legend (Tables 1-3 4) (39,43,45,46,53,57,60,64,(76)(77)(78)(79)(80). The available evidence is unclear whether lesser resection increases recurrence risk.…”
Section: Survivalmentioning
confidence: 99%
“…Compounding the challenge of impartial comparison, studies evaluating sublobar resection and lobectomy often did not include enough patients to parse out anatomic location, such that an upper lobectomy was compared to lower lobe segmentectomy on the opposite side and vice versa. While a retrospective study compared only lower lobectomy to superior segmentectomy 31 and found no difference in overall or disease‐free survival, small numbers of patients continued to make it evident that randomized controlled data would be best to address this now decades‐old debate. Senior thoracic surgeons pointed the greater thoracic oncology community to the outcome of two major Phase III randomized trials as the best hope in drawing clear conclusions, the Japanese Cooperative Oncology Group (JCOG) trial 0802 33 and the Cancer and Leukemia Group‐B (CALGB) trial 140503 34…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective series from larger academic institutions and databases began to emerge, some suggesting overall and recurrence-free survival (RFS) were similar between sublobar resection and lobectomy, with data conflicting on whether or not segmentectomy and wedge resection were equivalent approaches that could be grouped en mass when compared to lobectomy. [24][25][26][27]31 So conflicting was the data, that it became apparent that defining and ensuring high-quality sublobar resection in clinical research was just as paramount to an "apples-to-apples" comparison as the lack of rib spreading was to defining VATS research a decade prior. For instance, one study indicated that up to 26% of VATS wedge resections were completed with 0 lymph nodes sampled 32 -hardly a "quality sublobar resection.…”
Section: Introductionmentioning
confidence: 99%